‘The Devil Made Me Do It’ Electus per Deus and Quasi-Occult Crime in South Africa - Kapp, Tristán (Religion compass, 2026)
This study interrogates the phenomenon of ‘occult crime’ in South Africa, focusing on the perspectives of crime such as Electus per Deus, the murder of Kirsty Theologo, Hansie Cronjé, and the context behind the assumed connection between criminal culpability, mens daemonica, and the occult. These beliefs frequently espouse individuals ascribing criminal actions to ‘demonic’ authority or spiritual possession, thus reinterpreting typical criminal culpability as inherently occult-related. Therefore, by examining the religious, psychological, and socio-economic factors that contribute to the development and continuation of such beliefs, espousing that ‘the Devil made me do it’ in the interpretation of motives in crime and criminality. Noteworthy examples such as the Krugersdorp murders, the Samurai sword murderer, the Klawer murderer, the murder of Rina Radloff, and others frequently suggest an occult motive for crime, according to mainstream news media. The paper therefore seeks to examine the influence of Afrikaner Christian religious narratives on the way individuals and communities understand responsibility, morality, and justice (vis-à-vis crime and criminality). Identifying select South African case studies and theoretical frameworks involving religion and news media to analyse why such popular inferences are made, based on Ward & Voas' ‘conspirituality’ and John Calvin's doctrine of election. This study also aims to establish an understanding of occult crime as a conspiracy theory in South Africa by examining the relationship between religious belief systems and criminal behaviour. Therefore, it provides accurate information on occultism and Satanism for future academic discussions and practical considerations in jurisprudence, criminology, and alternative religious discourse in South Africa.